The Ickabog - Rowling, J. K. (Scholastic Inc., 2020)
As the legend of the fearsome Ickabog spreads terror in the peaceful kingdom of Cornucopia, best friends Bert and Daisy set out to discover the truth and bring happiness back to the kingdom.